2002
DOI: 10.1136/heart.88.4.401
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery stretch versus deep injury in the development of in-stent neointima

Abstract: Objective: To investigate the relative importance of stent induced arterial stretch and deep injury to the development of in-stent neointima. Setting: Normal porcine coronary arteries Methods: 30 BiodivYsio stents (Biocompatibles) were deployed at a stent to artery ratio of 1.25:1 (a moderate injury) and harvested at 28 days. Multiple serial cross sections were analysed morphometrically and the neointimal areas were correlated with the type and degree of injury. Results: Arterial stretch occurred in 78% of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 14 publications
8
109
0
3
Order By: Relevance
“…[19][20][21] It is not clear how much the underlying atherosclerotic plaques contribute to in-stent restenosis, but both the deep injury and the vessel stretch were shown to trigger the development of in-stent neointima in even normal coronary arteries. 22) Although maximum deployment pressures were not different between the two groups, an additional external force on the vessel wall might have caused a deeper injury in the MB group. Furthermore, the persistence of external compression in MB constitutes an important difference between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] It is not clear how much the underlying atherosclerotic plaques contribute to in-stent restenosis, but both the deep injury and the vessel stretch were shown to trigger the development of in-stent neointima in even normal coronary arteries. 22) Although maximum deployment pressures were not different between the two groups, an additional external force on the vessel wall might have caused a deeper injury in the MB group. Furthermore, the persistence of external compression in MB constitutes an important difference between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…7,22,23,32,35,46,77,81,82,86 The mechanical impact of the investigated stents was evaluated in terms of the equivalent von Mises stress (ES) distribution predicted in the artery wall. The ES is calculated as follows:…”
Section: Analysis Of Balloon-expandable Coronary Stentsmentioning
confidence: 99%
“…Over the past two decades, several clinical studies have identified strong correlations between neointimal hyperplasia following coronary stent deployment and both stent-induced arterial injury 7,22,23,32,35,46,77,81,82,86 and altered vessel hemodynamics. 6,17,18,20,21,52,71,79,88 In light of these observations, a significant body of research has been carried out in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In truth, the damage of the internal elastic lamina (border between intima and media) or external elastic lamina (border between media and adventitia) has been strongly correlated with neointimal growth. This deep injury concept points to media and adventitia (Gunn et al, 2002). The expansion of a stent within an eccentric artery induced considerably higher stresses in these two vessel layers.…”
Section: Stress Profiles In the Arterial Layersmentioning
confidence: 99%